Answer
To find the average rate of change of a function between two values, use the formula:
\[
\text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a}
\]
1. Identify the function and the two points \( a \) and \( b \).
2. Calculate \( f(a) \) and \( f(b) \).
3. Plug these values into the formula and simplify to find the average rate of change.
**Example:**
For \( f(x) = x^2 + 3x + 2 \) between \( x = 1 \) and \( x = 4 \):
\[
\text{Average Rate of Change} = \frac{30 - 6}{4 - 1} = 8
\]
So, the average rate of change is **8**.
Solution
To determine the **average rate of change** of a function between two given values of the variable, you can use the following formula:
\[
\text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a}
\]
Here:
- \( f(x) \) is the function.
- \( a \) and \( b \) are the two values of the variable between which you're calculating the average rate of change.
- \( f(a) \) is the value of the function at \( x = a \).
- \( f(b) \) is the value of the function at \( x = b \).
### **Step-by-Step Process**
1. **Identify the Function and Interval:**
- Determine the function \( f(x) \).
- Identify the two points \( a \) and \( b \) between which you want to find the average rate of change.
2. **Calculate \( f(a) \) and \( f(b) \):**
- Substitute \( a \) into the function to find \( f(a) \).
- Substitute \( b \) into the function to find \( f(b) \).
3. **Apply the Formula:**
- Plug the values of \( f(a) \), \( f(b) \), \( a \), and \( b \) into the average rate of change formula.
4. **Simplify:**
- Perform the subtraction and division to find the average rate of change.
### **Example**
Let's go through an example for clarity.
**Function:** \( f(x) = x^2 + 3x + 2 \)
**Interval:** Between \( x = 1 \) and \( x = 4 \)
**Step 1:** Identify \( a = 1 \) and \( b = 4 \).
**Step 2:** Calculate \( f(1) \) and \( f(4) \).
- \( f(1) = (1)^2 + 3(1) + 2 = 1 + 3 + 2 = 6 \)
- \( f(4) = (4)^2 + 3(4) + 2 = 16 + 12 + 2 = 30 \)
**Step 3:** Apply the formula.
\[
\text{Average Rate of Change} = \frac{f(4) - f(1)}{4 - 1} = \frac{30 - 6}{3} = \frac{24}{3} = 8
\]
**Conclusion:** The average rate of change of the function \( f(x) = x^2 + 3x + 2 \) between \( x = 1 \) and \( x = 4 \) is **8**.
### **Interpretation**
The average rate of change represents the average slope of the function over the interval \([a, b]\). In the example above, it means that, on average, the function increases by 8 units in function value for each unit increase in \( x \) between \( x = 1 \) and \( x = 4 \).
### **Additional Notes**
- The average rate of change is closely related to the concept of the **derivative**, which represents the instantaneous rate of change at a specific point.
- For linear functions, the average rate of change is constant and is equal to the slope of the line.
- For non-linear functions, the average rate of change gives a sense of the overall trend between two points but doesn't capture variations within the interval.
If you have a specific function and interval you'd like to analyze, feel free to provide them, and I can walk you through the calculation!
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution